Safety and efficacy of acupuncture for mild cognitive impairment: a study protocol for clinical study - Kim, Jae-Hong; Shin, Jeong-Cheol; Kim, Ae-Ran; Seo, Bok-Nam; Park, Gwang-Cheon; Kang, Byoung-Kab; Lee, Jeong-Soon (Frontiers in Neurology, 2024)
Background Mild cognitive impairment (MCI) is an intermediary condition between typical cognitive decline that occurs owing to aging and dementia. It is necessary to implement an intervention to slow the progression from MCI to Alzheimer’s disease. This manuscript reports the protocol for a clinical trial on the effect of acupuncture in patients with MCI. Methods The trial will be a randomized, prospective, parallel-arm, active-controlled trial. Sixty-four patients with MCI will be randomized to the Rehacom or acupuncture group (n = 32 each). The participants in the acupuncture group will receive electroacupuncture at GV24 (Shenting) and GV20 (Baihui) and acupuncture at EX-HN1 (Sishencong) once (30 min) a day, twice per week for 12 weeks. The patients in the Rehacom group will receive computerized cognitive rehabilitation using RehaCom software once (30 min) daily, twice weekly for 12 weeks. The primary outcome measure is the change in the Montreal Cognitive Assessment Scale score. The secondary outcome measures are the Geriatric Depression Scale, Alzheimer’s Disease Assessment Scale-Korean version-cognitive subscale-3 scores, and European Quality of Life Five Dimensions Five Level Scale. The safety outcomes will include the incidence of adverse events, blood pressure, blood chemistry parameters, and pulse rate. The efficacy outcome will be assessed at baseline and at six weeks, 13 weeks, and 24 weeks after baseline. Discussion The findings of this protocol will provide information regarding the effects of acupuncture on MCI. Clinical trial registration <ext-link xlink:href="https://cris.nih.go.kr/cris/search/detailSearch.do?search_lang=E&focus=reset_12&search_page=M&pageSize=10&page=undefined&seq=25579&status=5&seq_group=25579" ext-link-type="uri" xmlns:xlink="http://www.w3.org/1999/xlink">https://cris.nih.go.kr/cris/search/detailSearch.do?search_lang=E&focus=reset_12&search_page=M&pageSize=10&page=undefined&seq=25579&status=5&seq_group=25579, KCT0008861.